Whatever It Takes: The Real Effects of Unconventional Monetary Policy - Acharya, Viral V; Eisert, Tim; Eufinger, Christian; Hirsch, Christian (Review of Financial Studies, 2019)
Abstract Launched in Summer 2012, the European Central Bank’s (ECB) Outright Monetary Transactions (OMT) program indirectly recapitalized European banks through its positive impact on periphery sovereign bonds. However, the stability reestablished in the banking sector did not fully translate into economic growth. We document zombie lending by banks that remained weakly capitalized even post-OMT. In turn, firms receiving loans used these funds not to undertake real economic activity, such as employment and investment, but to build cash reserves. Creditworthy firms in industries with a high zombie firm prevalence significantly suffered from this credit misallocation, which further slowed the economic recovery. Received March 21, 2018; editorial decision November 13, 2018 by Editor Philip Strahan. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.